ETIKA BISNIS ISLAM DALAM TINJAUAN AL-QUR'AN DAN HADITS: Islamic Business Ethics in a Review of the Qur'an and Hadith - Nurul Huda, Siti; Ihwanudin, Nandang (Asosiasi Dosen PTKIS Indonesia, 2022)
This study discusses Islamic business ethics, which is prohibited in the Qur'an and Hadith. The purpose of this study is to convince businessmen that the purpose of business in Islam is not only material achievement, but the safety of the world and the hereafter, of course, by knowing the verses of the Qur'an and Hadith about business that is forbidden by businessmen, so that it will always become the concern of Islamic business ethics to achieve the value of victory (falah). The method used in this research is descriptive method. Islam has very great principles in business including monotheism. If all business people have strong monotheism, surely they will not carry out prohibited transactions and there will be equal justice.